PENGARUH KOLKISIN TERHADAP PERKECAMBAHAN DAN JUMLAH STOMATA TANAMAN JAGUNG LOKAL (Zea mays L.) DI KABUPATEN TIMOR TENGAH UTARA - Polikarpia Wilhelmina Bani; Florayani Sifa; Yolanda Getrudis Naisumu (Saintek Lahan Kering, 2022)
North Central Timor (TTU) Regency as one of the regencies in East Nusa Tenggara Province that prioritizes the development of corn plants.This is because local corn has a longer growing period than hybrid corn, so people are less likely to cultivate it. There are many ways to increase maize productivity by plant breeding, which has been widely used, namely the formation of polyploidy plants using the chemical colchicine. It is also known that local maize productivity can be increased by using colchisine. The purpose of this study was to determine the effect of colcisine on germination and number of stomata of local maize (Zea mays, L.) in North Central Timor Regency. Data analisis in this study used variance (Anova) and Completely Randomized Design (CRD). The average treatment was further tested using Duncan Multiple Range Test (DMRT) with a significant level of 5%. Data analisis using SAS 9.1 program. The results of this study indicate that there is a difference between colchisine treatment and corn varieties. The results of the DMRT further test with colchisine treatment significanty affected the character of the observation of stone corn root length with a colchisine concentration of 40% (K1) and the colchisine treatment also significantly affected the observational character of the number of stomata of corn on the first and 7th leaves. Colchisine treatment had a significant effect on the germination of local maize (Zea mays, L.), the number of stomata on the observed characters of the first leaf and the 7th leaf and had no effect on the stomata type of local maize (Zea mays, L.).